Prevalence and determinants of zero vegetable and fruit consumption among Bangladeshi children under 2: a community-based cross-sectional study - Md Fuad Al Fidah; Syeda Sumaiya Efa; Md Nafis Fuad; Sharif Mohammad (BMJ Paediatrics Open, 2025)
This study estimated the prevalence and determinants of zero vegetable and fruit (ZVF) consumption among children aged 6–23 months, using data from the 2019 Multiple Indicator Cluster Survey, Bangladesh (n=6668). The prevalence of ZVF was 44.1%. Lower odds of ZVF were observed among older children and those whose mothers had higher levels of education, media exposure or belonged to wealthier households. In contrast, children with recent illnesses and urban residents had higher odds of ZVF. Targeted interventions for younger and socioeconomically disadvantaged children, alongside maternal nutrition education, are essential to promote fruit and vegetable intake in early childhood.